ACCOUNTING PRINCIPLES UNDERLYING CORPORATE FINANCIAL STATEMENTS. (The Accounting Review, 1942)
Abstract The article focuses on accounting principles underlying corporate financial statements. The present executive committee of the American Accounting Association believes that efforts the association makes, justifies faith in the continued orderly development of accounting principles and in the ability of accountants to guide this development in accordance with their own high sense of social responsibility. Indeed, the committee believes that basic accounting concepts should be given continuous study, to the end that the needs of those concerned with corporate reports, whether as managers, investors, members of regulatory bodies or the general public, may be best served. In the corporate field the most important use of accounting lies in the preparation of statements of financial position and of operating results. So many vital decisions of business and government depend on the interpretation of such statements that they have come to be of prime economic and social significance. Business enterprises differ in nature and in application of principles.